Distal biceps repair through a single incision with the use of a knotless cortical button device: Mid-term results. (December 2022) - Assiotis, Angelos; French, Jonathan; Edwards, Gray; McCann, Philip A; Chalk, Naomi; Amirfeyz, Rouin
Background: Distal biceps rupture presents with an increasing incidence and evidence suggests that although a surgical repair is not mandatory, it results in superior functional outcomes when compared to non-operative management. As implant technology has advanced, several devices have been utilised and studied in managing this pathology. We present our single-centre experience with the use of the ToggleLoc Ziploop reattachment device, a knotless cortical button implant, using a single-incision technique. Methods: Retrospective series of 70 consecutive distal biceps tendon repairs, at a mean follow-up of 45.6 months after surgery, using a standardised single implant, single-incision technique, and post-operative rehabilitation programme. Results: There was one (1.4%) re-rupture in our patient cohort. The range of motion was complete in all patients except for one patient who had symptomatic heterotopic ossification, causing limitation in pronation. Complications were minor with the commonest being transient neuropraxia of the lateral cutaneous nerve of the forearm. The mean Oxford elbow score was 46.9 out of 48, and the patient global impression of change scale was 7 out of 7 in 77% of cases. Conclusion: Our data support this technique and implant combination when dealing with acute and chronic distal biceps tendon rupture.